Corporate governance structure, bank externalities and sensitivity of non-performing loans in Nigeria - Alex Adegboye; Stephen Ojeka; Kofo Adegboye (Cogent Economics & Finance, 2020)
This study highlights the effect of corporate governance structure and bank externalities on non-performing loans in Nigeria covering the period 2009-2017. This study constructs corporate governance index for Nigerian Banks using Principal Component Analysis to establish the influence of corporate governance structure on non-performing loans. This study conducts a panel data analysis using static and dynamic estimators to examine the sensitivity of non-performing loans and corporate governance structure. From the empirical analysis, corporate governance structure of banks in Nigeria has a negative and significant influence on non-performing loans in Nigerian banks. This result reveals that sound corporate governance structure enhances the loan quality and bank stability. In addition, the study affirms that stringent policy imposed by the bank regulators has a negative impact on non-performing loans. Thus, effective corporate governance mechanism and bank regulations could help to curb excessive risk appetite that could mutilate probable performance and loan quality. This study recommends that banks should continue to implement high quality of corporate governance mechanism with positive effects at eliminating excessive risk-taking.
Keywords: 330; bank externalities; corporate governance index; non-performing loans; principal component analysis